Maltrato psicológico y su relación con la autoestima de los niños y niñas de primer año de educación básica de la escuela fiscal “Luz Victoria Rivera de Mora” del cantón Balsas, provincia de el Oro. Periodo lectivo 2014 – 2015”. Lineamientos propositivos - Suarez Silva, Yuri Elizabeth (2015)
This research was developed in the Public School "Luz Rivera De Mora Victoria" located in Canton rafts, in the province of El Oro, called: “MALTRATO PSICOLÓGICO Y SU RELACIÓN CON LA AUTOESTIMA DE LOS NIÑOS Y NIÑAS DE PRIMER AÑO DE EDUCACIÓN BÁSICA DE LA ESCUELA FISCAL “LUZ VICTORIA RIVERA DE MORA” DEL CANTÓN BALSAS, PROVINCIA DE EL ORO. PERIODO LECTIVO 2014 – 2015”. LINEAMIENTOS PROPOSITIVOS. The central issue is: What is the relationship between self-esteem and psychological abuse of children First-Year Basic Education Public School "Victoria Luz Rivera De Mora" the Balsas Canton, Province of El Oro semester. 2014 - 2015. Guidelines proactive? issue that was discussed in the course of the investigation, it has been structured and developed in accordance with Regulation of Academic System of the National University of Loja. The overall objective was formulated; analyze psychological abuse and its relationship with self-esteem. The methods used were scientific, analytical method - Synthetic, inductive, deductive and descriptive. The survey of Parents, to identify the type of psychological abuse; and Self-Esteem Test Lewis R. Aiken applied to children to assess self-esteem. With the implementation of the research instruments the following results were obtained: 52% Parents evaluated psychologically mistreat their children actively; and 47% passively mistreated. Psychological Abuse is evident in homes. Actively are the behaviors and speeches involving insult, terrorize, cause fear. Passively it refers to the omission of care, affection and words that your child needs for healthy development; it corresponds to situations of violence by omission, isolation and ignore. 51% of children evaluated have a high self-esteem and low self-esteem 49%. High Self-esteem is manifested when they are happy, independent, have confidence, tolerate frustration, can properly handle criticism or ridicule from their peers. Children with low self-esteem, is depressed, lack confidence, retract, away from other children and are not proud of their work.